Charity Colonoscopy Event and Fund in Singapore: A Novel Method to Raise Awareness of Colorectal Cancer Screening - Francis Zheng Yi Yee (World Journal of Colorectal Surgery)
Background: Despite the improvements in the incidence rate and mortality of colorectal cancer in Singapore, most cases are still diagnosed at later stages. This suggests limitations in the uptake of cancer screening, relating to suboptimal population awareness, unfamiliarity with tests, or cost concerns.